Strategies for management of pests and diseases of snap beans in Latin America - Cardona, C.; Pastor Corrales, Marcial A. (International Center for Tropical Agriculture, 1990)
Pests and diseases are important production constraints of snap beans in tropical and subtropical regions of the world. Among the most important conditions favoring their development are climate, planting susceptible varieties in monoculture over entire regions, staggered planting dates, and planting infected seed. In addition, indiscriminate use of chemicals kills beneficial insects and induces resistance. Among the most important pests are whiteflies, leafminers, leafhoppers, pod borers, chrysomelids, cutworms, crickets, mites and bruchids. In highland regions with cool climates, anthracnose, ascochyta blight, halo blight, and white and gray mold are the most important diseases during rainy growing cycles. Rust, powdery mildew and southern blight are prevalent during the drier cycles. At lower altitudes with warmer climates, rust, bacterial blight and powdery mildew are the most important diseases. However, in the rainy, tropical lowlands, web blight is the most important disease. Disease and insect control should pursue an integrated approach that includes: a broadening of the genetic base; more rational chemical control; the use of clean seed; and rotations with crops that are not hosts for snap bean pests and diseases. (AS)